Identification, characterization, and developmental regulation of two storage proteins in the bamboo borer Omphisa fuscidentalis - Tungjitwitayakul J. (2014)
Two insect storage proteins, OfSP1 (75 kDa) and OfSP2 (72 kDa), were purified using three different chromatographies from the hemolymph of Omphisa fuscidentalis larvae during diapause, and their genes were cloned. OfSP1 and OfSP2 concentrations in the hemolymph were high during diapause. During pupation, OfSP1 levels decreased in the male hemolymph and disappeared from the female hemolymph. OfSP1 and OfSP2 mRNA levels in the fat bodies were low during the third instar, but increased greatly during the fourth and fifth larval instars. During diapause, mRNA expression continued at a lower level than during the feeding period. The injection of 20-hydroxyecdysone (20E) into diapausing larvae caused an increase in OfSP1 and OfSP2 mRNA levels 2-3 days post-injection, followed by a decrease in expression until pupation, which occurred 2-4 days thereafter. When larvae were treated with juvenile-hormone analog (JHA), OfSP1 and OfSP2 mRNA levels gradually decreased until the onset of pupation. In Omphisa, OfSP1 and OfSP2 proteins are produced and released by the larval fat bodies in the fourth and fifth-instar larvae, and the proteins accumulate in the hemolymph until the insects enter diapause. OfSP1 may be reabsorbed by the fat bodies at the end of diapause for subsequent re-use during pupation. © 2007 Elsevier Ltd. All rights reserved.